2022
DOI: 10.14715/cmb/2021.67.4.1
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PCAT1 might coordinate ZNF217 to promote CRC adhesion and invasion through regulating MTA2/MTA3/Snai1/E-cadherin signaling

Abstract: LncRNA prostate cancer-associated transcript 1 (PCAT1) is a well-known oncogene, but the mechanisms of exosomes PCAT1 in colorectal cancer (CRC) remain largely unknown. Thus, the mechanisms of exosomes lncRNA PCAT1 were investigated. The expressions of exosomes lncRNA PCAT1 in tissues from stage 0-I and stage II-III CRC patients, and intestinal epithelial cell line FHC and two CRC cell lines, HT29 and HCT8 were measured by real-time quantitative PCR. The effects of lncRNA PCAT1 on adhesion and invasion of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Similarly, ZNF143 suppresses cell apoptosis and promotes proliferation in gastric cancer via ROS/p53 axis 59 . In accordance with these observations, ZNF217 may promote tumor progression by inducing cell migration and invasion in OVCA and CRC 76,101 . Considering the dysregulated expression of ZNFs in multiple cancer types, the possible explanation is an unknown factor that may interact with ZNFs in carcinogenesis.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly, ZNF143 suppresses cell apoptosis and promotes proliferation in gastric cancer via ROS/p53 axis 59 . In accordance with these observations, ZNF217 may promote tumor progression by inducing cell migration and invasion in OVCA and CRC 76,101 . Considering the dysregulated expression of ZNFs in multiple cancer types, the possible explanation is an unknown factor that may interact with ZNFs in carcinogenesis.…”
Section: Discussionsupporting
confidence: 61%
“…These results demonstrate that miR193a‐5p‐mediated inhibition of ZNF746/c‐Myc signaling in Morusin induces apoptosis in CRCs 75 . LncRNA prostate cancer‐associated transcript 1 (PCAT1) increases ZNF217 expression to promote the adhesion and invasion of CRC through activating the EMT‐associated MTA2/MTA3/Snai1/E‐cadherin signaling pathway 76 …”
Section: Role Of Znfs In Different Tumorsmentioning
confidence: 73%
See 1 more Smart Citation
“…The lncRNA prostate-associated transcript 1 (PCAT1) is a well-known oncogene that was found to be upregulated in colorectal cancer tissues and exosomes derived from colorectal patients [ 85 ]. The same study identified that ZNF217 expression levels were negatively regulated by lncRNA PCAT1 silencing.…”
Section: Noncoding Rna Network Target Znf217 Mrna ...mentioning
confidence: 99%
“…The same study identified that ZNF217 expression levels were negatively regulated by lncRNA PCAT1 silencing. The study suggested that lncRNA PCAT1 might co-ordinate ZNF217 to enhance colorectal cancer progression through the regulation of an EMT axis involving two metastasis-associated 1 family members (MTA2/MTA3) and Snai1/E-cadherin ( Figure 3 ) [ 85 ]. While the authors argue a putative physical interaction between lncRNA PCAT1 and ZNF217 , future work is further needed to confirm and to unravel the impact of any possible physical interaction between ZNF217 and any specific lncRNA.…”
Section: Noncoding Rna Network Target Znf217 Mrna ...mentioning
confidence: 99%